Девушка из нежной стали: роман / Татьяна Алюшина - Алюшина Татьяна Александровна (Экcмо, 2022)
Экземпляры: ф.9 (2024) / Инвентарный номер: 60106 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: А 59 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=411.2)6